Classe Hospitalar: Do Território Ao Lugar Em Tempos E Espaços Educacionais - Lima, Angelica Macedo Lozano [UNIFESP] (2018)
This Research Relates To The Place That Embraces The Relations Between The Subjects In The Hospital Classroom. To Understand It, We Worked With The Class Starting From The Teacher's And Student's Movement From Their School Of Origin To Relate With Each Other In This Other Place, A Process Which We Call Deterritorialization. From This Concept, Adopted By The Geography Of Gilles Deleuze And Felix Guattari, We Approach The Other Concepts Related To Research And Subjects Of Action: Territory And Place. In This Way, We Thought The Deployment Of The Investigation Should Be To Understand How The Teachers Related To Each Other And How They Modified Their Practices According To This Spatial And Relational Displacement. Our Purpose Was To Find Out If, Because Of The Deterritorialization Of These Subjects, A Place Was Created - Which Is The Hospital Classroom -, And, If This Fact Is Concrete, To Understand How The Practices Of The Teachers Were Modified In This Environment. The Methodology Was Assisted By Interviews And